Preventative detention and control orders under federal law: the case for a bill of rights - Fairall, Paul; Lacey, W. (Melbourne University, 2007)
Federal laws passed since the 11 September 2001 attacks in the United States represent an extraordinary challenge for human rights protection in Australia. The legislative erosion of rights traditionally assumed as being fundamental within common law countries lies at the heart of this challenge. This article focuses on extraordinary measures recently added to the package of anti-terrorism laws: preventative detention orders; prohibited contact orders; and control orders. These measures were added to Part 5.3 of the Schedule to the Criminal Code Act 1995 (Cth) by the Anti-Terrorism Act [No 2] 2005 (Cth), and directly and explicitly remove or interfere with a number of individual rights. In this article we argue that the threat to human rights posed by such measures derives not only from their legislative enactment and form. The threat is heightened by the dominance of a positivistic legalism in the approach of the High Court of Australia — an approach that treats the constitutional text as the foundation of the rule of law in Australia, as opposed to the supreme manifestation of the rule of law that rests on a broader, but less explicit, foundation of constitutionalism. In this respect, the presence of a written Constitution has hindered the protection of rights to the extent that the principle of legality operates within a textual straitjacket. Until such time as Australia adopts a bill of rights at the national level, or there occurs an unlikely shift in the jurisprudential approach of the High Court, the Court will have little room to manoeuvre out of its positivistic corner when faced with other extraordinary legislative measures.